PENGARUH TERAPI MUSIK DAN MASASE PUNGGUNG TERHADAP NYERI KALA I FASE AKTIF PADA NULIPARA DI RUMAH SAKIT BETHESDA YOGYAKARTA - Isnanto, Isnanto; Pinzon, Rizaldi (Jurnal Kesehatan, 2018)
Background : Labor is a physiological event that can cause a severe pain in the process. Many techniques are done to reduce the pain, pharmacologically and non-pharmacologically. Pharmacological therapy tends to be more expensive than non-pharmacological one. Non-pharmacological method can increase satisfaction during labor if mother can control her feeling and anxiety. Musical therapy and back massage are non-pharmacological techniques that can increase mother’s comfort in the process of labor and have effective in?uence on labor experience. Objective : The research was conducted to know the effect of musical therapy and back massage toward intensity of pain in nulipara during stage 1 active phase of labor in delivery room of Bethesda Hospital. Consecutive sampling technique was applied with 30 respondents, 15 in musical therapy group and 15 in back massage group. Methods : It was a quasi experiment reasearch with two groups comparison pretest-posttest design. There were two observations, before and after treatment. Data analysis was done with paired t-test. Results : The result shows either musical therapy or back massage gives good effect in reducing pain in nulipara during stage 1 active phase of labor in delivery room of Bethesda Hospital during July-September 2017. The signifcant value (Sig. (2-tailed) is 0.000 or (p,0.05) which means there is an effect on both interventions toward intensity of pain in nulipara during stage 1 active phase of labor. Nevertheless, the mean of pain scale in pre and post therapy for musical therapy group is bigger than back massage group that is 3,267 for musical therapy group and 2,000 forback massage group. The t-value of musical therapy group is bigger (17,978) compared to back massage group (8,367). Conclusion : Therefore musical therapy has bigger effect in reducing pain compared to back massage in nulipara during stage 1 active phase of labor in delivery room of Bethesda Hospital during July-September 2017.Keywords: Labor - Pain - Musical Therapy - Back Massage